2017
DOI: 10.2196/rehab.6901
|View full text |Cite
|
Sign up to set email alerts
|

Counting Grasping Action Using Force Myography: An Exploratory Study With Healthy Individuals

Abstract: BackgroundFunctional arm movements generally require grasping an object. The possibility of detecting and counting the action of grasping is believed to be of importance for individual with motor function deficits of the arm, as it could be an indication of the number of the functional arm movements performed by the individuals during rehabilitation. In this exploratory work, the feasibility of using armbands recording radial displacements of forearm muscles and tendons (ie, force myography, FMG) to estimate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 55 publications
(77 reference statements)
2
23
0
Order By: Relevance
“…It has been demonstrated that unlike EMG, performance of FMG does not rely heavily on feature extraction (Belyea et al, 2018) which has led to the common use of raw FMG signals for gesture recognition (Radmand et al, 2016;Ferigo et al, 2017;Jiang et al, 2017;Xiao and Menon, 2017a;Belyea et al, 2018). Since the focus of this study was channel selection, feature extraction was not considered in this experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that unlike EMG, performance of FMG does not rely heavily on feature extraction (Belyea et al, 2018) which has led to the common use of raw FMG signals for gesture recognition (Radmand et al, 2016;Ferigo et al, 2017;Jiang et al, 2017;Xiao and Menon, 2017a;Belyea et al, 2018). Since the focus of this study was channel selection, feature extraction was not considered in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Various classification methods have been assessed for FMG controlled prostheses, some of the commonly used ones of which are linear discriminant analysis (LDA), support vector machine (SVM), and k-nearest neighbors (KNN) (Naik et al, 2015;Ahmadizadeh et al, 2017). Amongst these, LDA is one of the most widely used classifiers due to its capability in separating different classes of gestures and also its computational efficiency (Cho et al, 2016;Radmand et al, 2016;Xiao and Menon, 2017a). A study by Ahmadizadeh et al compared performance of the three aforementioned classifiers for gesture classification using FMG data and determined LDA to be the classifier of choice for their study (Ahmadizadeh et al, 2017).…”
Section: Application Backgroundmentioning
confidence: 99%
“…All ML models were trained using data collected while performing static singleton gestures ( Table 2). These models previously demonstrated good accuracy in hand gesture classification based on FMG data [17,47,48]. ML models were then used to identify the singleton gestures performed during compound gestures or dynamic motions.…”
Section: Gesture Classification Using Machine Learningmentioning
confidence: 99%
“…In literature, there are some reported works on using FMG to detect upper body and lower body movements Cho et al (2016); Kadkhodayan et al (2016); Xiao and Menon (2017); Sadarangani and Menon (2017); Islam and Bai (2017); Jiang et al (2016); Xiao et al (2014); Islam et al (2018). However, this approach has not been used yet for payload estimation to control upperbody exoskeleton in load carrying tasks.…”
Section: Introductionmentioning
confidence: 99%